COMPLETE ASYMPTOTICS OF THE DEVIATION OF A CLASS OF DIFFERENTIABLE FUNCTIONS FROM THE SET OF THEIR HARMONIC POISSON INTEGRALS - Kharkevych, Yurii I.; Zhyhallo, Kostiantyn M.; Харкевич, Юрій Іліодорович; Жигалло, Костянтин Миколайович (Ukrainian Mathematical Journal, 2002)
On a class of differentiable functions W r and the class of functions conjugate to them, we obtain a complete asymptotic expansion of the upper bounds of deviations of the harmonic Poisson integrals of the functions considered.